Antecedents of entrepreneurial processes of causation and opportunity recognition in building material retail trade in Nigeria - Makama, Adamu Ado; Abdul, Mohani B.; Sambasivan, Murali; Raja Yusof, Raja Nerina (Mediterranean Center of Social and Educational Research, 2016)
Entrepreneurial opportunity has been a highly contentious construct among entrepreneurial scholars. Some argue that opportunity is objective - it exists independent of entrepreneurs and it can be exploited through the causation process (consistent with opportunity as discovery) which is based on rational decision model. Some argue that opportunity cannot exist independent of entrepreneurs. The basic objective of this study is to conduct a quantitative study to examine the antecedents of causation and study the impact of causation on opportunity recognition. The antecedents examined in this study are: entrepreneur’s education, entrepreneur’s special education, entrepreneur’s personality traits, and entrepreneur’s management skills. The population for this study was Nigerian entrepreneurs dealing in building materials. A questionnaire was designed and sent to 1,950 Entrepreneurs in the Building Material Industry Trade. Results of the study indicate that (1) the antecedents influence causation process and (2) causation process influences entrepreneur’s ability to recognize opportunities.